“Periosteum: An imaging review” - Carlos Henrique Maia Ferreira Alencar (European Journal of Radiology Open, 2020)
Periosteum is a fibrous sheath, coating the external bone, except in the articular surfaces, tendon insertions and sesamoid bone surface¹. It changes its aspects and characteristics with aging, becoming progressively less elastic and more firm. It is composed of two different layers: outer fibrous (firm, collagen-filled) and inner proliferative (cambium, containing osteoprogenitor cells)². Four vascular systems are responsible for the blood supply of the periosteum: the intrinsic periosteal system, located between fibrous and proliferative layer; the periosteocortical, the main nutritional arteries of the periosteum; the musculoperiosteal, responsible for the callus formation after fractures; the fascioperiosteal, specifically for each bone.³ It is crucial to bone formation and resorption, reacting to insults in the cortical bone, such as tumors, infections, traumas, medications and arthritic diseases. The aggressiveness of the reaction can be suggested by its radiological aspect and appearance4. The periosteum in children is looser compared to adults, resulting in earlier and more exuberant reactions. All these aspects will be detailed, so the essential information all radiologists need to know will be discussed.